2014
DOI: 10.1016/j.dsr2.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton and pigment studies in the Bay of Biscay and English Channel

Abstract: a b s t r a c tDuring the final year (2010) of the MV Pride of Bilbao (PoB) ferry operation between Portsmouth (UK) and Bilbao (Spain) a comprehensive phytoplankton data set was collected based on pigments and taxonomy measurements. The work was in support of the EU project ProTool (http://www.protool-project.eu) that aimed to develop an automated system for measuring primary productivity from ships of opportunity. Not unexpectedly, the biological patterns relate to the hydrographic conditions and in general, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Our morphological observation also identified dinoflagellates as another major phytoplankton group (Supplementary Table 1) which agreed with a previous study (Madhupratap et al, 2003). Previous studies carried out in the Chesapeake Bay (MD, United States), the Jiaozhou Bay (Qingdao, China), and the Bay of Biscay (western coast of France) have shown that morphologically identified diatoms, as well as dinoflagellates, were consistently dominant and diverse in different ecosystems (Marshall and Lacouture, 1986; Shen, 2001; Smythe-Wright et al, 2014). However, dinoflagellates were under-represented in our molecular analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our morphological observation also identified dinoflagellates as another major phytoplankton group (Supplementary Table 1) which agreed with a previous study (Madhupratap et al, 2003). Previous studies carried out in the Chesapeake Bay (MD, United States), the Jiaozhou Bay (Qingdao, China), and the Bay of Biscay (western coast of France) have shown that morphologically identified diatoms, as well as dinoflagellates, were consistently dominant and diverse in different ecosystems (Marshall and Lacouture, 1986; Shen, 2001; Smythe-Wright et al, 2014). However, dinoflagellates were under-represented in our molecular analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Water samples from the ferry were also filtered and analysed ashore using High Performance Liquid Chromatography (HPLC) for phytoplankton pigments (reported in Smythe-Wright et al, 2014). Additionally on day 203 (July 22 nd ), two samples of water were collected by the Environmental Health and Pollution Regulation Unit seven miles to the west of Guernsey; these were sent to CEFAS Lowestoft for species identification using microscopy and cell counts, using a similar method to the one used for samples collected from the ferry.…”
Section: Bloom Identificationmentioning
confidence: 99%
“…(Ch) and Leptocylindrus minimus (Lem)) were identified as the protagonists in community changes between 2003-2005, 2006 and 2007-2014. All of them are commonly found in the Bay of Biscay (Lampert et al, 2002;Lunven et al, 2005;Quevedo and Anadón, 2000;Smythe-Wright et al, 2014). Even though, they were present at the same period of the year (spring) and some of them (such as Ps) are considered as cosmopolite (Trainer et al, 2012), the present study showed they occupied different ecological niches and responded differently to environmental conditions.…”
Section: Dynamics In Microphytoplankton Species Ecological Nichesmentioning
confidence: 56%